Aplicación de técnicas de lubricación predictivas en Grupos Electrógenos - D. Fernández-Fernández; F. Mourdoch-Misa (Ingeniería Mecánica, 2009)
Es conocido que una de las principales medidas adoptadas en el país es la generación de grupos electrógenos que utilizan combustible diesel, con potencias que oscilan entre 0.5 y 18 MW. Marcas como MTU (Mercedes Benz), GUASCOR, HUNDAY, MAN se encuentran entre las más representativas y estos grupos están formados básicamente por un motor de combustión interna (MCI) acoplado a un generador de electricidad de corriente alterna.Es una práctica internacional comúnmente aceptada utilizar la información derivada del análisis del aceite para definir el momento óptimo para efectuar el cambio de aceite, con el consiguiente ahorro que esto representa, así como identificar posibles problemas de funcionamiento, causas probables y plan de medidas a ejecutar. De hecho, para lograr mayor efectividad, dichas técnicas se combinan con otros métodos de diagnóstico tales como el diagnóstico por vibraciones, termografía, etc.En el presente trabajo se exponen los resultados derivados de la aplicación en los motores de los grupos electrógenos GUASCOR, aplicando técnicas predictivas de lubricación combinadas con técnicas de análisis de las vibraciones.It is well known that one of the main measures adopted within the Energetic Revolution is the inclusion to the power generation of Diessel driven electric plant which use fuel and diesel combustibles of a potency that oscillates between o.5 and 18 MW. Brands such as MTU (Mercedes Benz), GUASCOR, HYUNDAY, and MAN are among the most representatives, and are basically made up by an internal combustion motor connected to an alternating current generator.However, it is internationally accepted to use the information derived from the oil analysis to define the best timing for changing it, which represents a consequently saving. This analysis helps also to identify possible malfunctioning problems, its probable causes and to execute a solution plan. In fact, to achieve a greater efficiency these analysis are combined with other techniques as diagnostic by vibrations, thermography, etc.This paper shows the results derived from the application of predictable lubrication techniques combined with analysis by vibration techniques in the GUASCIt is well known that one of the main measures adopted within the Energetic Revolution is the inclusion to the power generation of Diessel driven electric plant which use fuel and diesel combustibles of a potency that oscillates between o.5 and 18 MW. Brands such as MTU (Mercedes Benz), GUASCOR, HYUNDAY, and MAN are among the most representatives, and are basically made up by an internal combustion motor connected to an alternating current generator.However, it is internationally accepted to use the information derived from the oil analysis to define the best timing for changing it, which represents a consequently saving. This analysis helps also to identify possible malfunctioning problems, its probable causes and to execute a solution plan. In fact, to achieve a greater efficiency these analysis are combined with other techniques as diagnostic by vibrations, thermography, etc.This paper shows the results derived from the application of predictable lubrication techniques combined with analysis by vibration techniques in the GUASC